ASSESSMENT OF TOTAL QUALITY MANAGEMENT OF CARE SERVICE BETWEEN INPATIENT AND PAEDIATRIC OUTPATIENTS IN URBAN AND RURAL AREA - Sujata Angela Singh; Dr. Kuldeep Singh Gurjar; Dr. Niyati Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The efficacy of Total Quality Management (TQM) in pediatric care is additionally emphasized by the changing terrain of quality enhancement approaches. The scarcity of chronic diseases, socioeconomic elements, and limitations in resources require inventive methods to enhance the quality of pediatric healthcare. The purpose of investigating the disparity in hospital service quality between inpatient and outpatient settings with a total of400 patients has been selected. 400 respondents have been selected from the various hospitals in the rural and urban area in Kolkata.Using a survey methodology, the distinction in the quality of inpatient and ambulatory pediatric healthcare services has been established. Only 80 respondents said there is an unbalanced distribution of pediatric services between in/ out settings in urban and rural areas. Analysis shows a difference in the provision of pediatric services across in on those settings in urban and rural locations. 80 of the respondents stated that there is an unequal distribution of paediatric services across in- patient and out-patient settings within the paediatric healthcare system in both urban and rural areas.The concentration of sophisticated care in centralized children's hospitals might cause a gap in pediatric services. On the other hand, most community practices and community hospitals provide some level of pediatric care, although the level varies from place to place.